β-blockers influence oncological outcomes in gastric cancer patients treated with neoadjuvant chemotherapy based on the pathological subtype: a retrospective cohort study - Crnovrsanin, Nerma; Zumsande, Sarah; Rompen, Ingmar F.; Schiefer, Sabine; Zimmer, Sarah; Hu, Wenjun; Arnscheidt, Johanna; Brinkmann, Fritz; Longerich, Thomas; Haag, Georg Martin; Schmidt, Thomas; Saeedi, Mohammed al; et al. (Annals of surgical oncology, 2025)
INTRODUCTION: Preclinical studies suggest that β-blockers (BBs), traditionally used for cardiovascular diseases, may improve cancer outcomes. This study assessed the effect of BB intake on oncological outcomes and response to chemotherapy in gastric cancer (GC) patients and the influence of ß2-adrenergic receptor (ADRB2) expression on local tumor innervation. - METHODS: We retrospectively analyzed the BB intake of 361 patients who underwent surgery with curative intent for GC after neoadjuvant chemotherapy at the University Hospital of Heidelberg. Resection specimens were analyzed and immunohistochemical stainings were performed to evaluate ADRB2 expression and neuronal markers (protein gene product 9 [PGP.9]). Survival rates were estimated using Kaplan-Meier curves, and multivariable Cox regression analysis was performed to control for confounding variables. - RESULTS: In patients with diffuse GC (DGC), BB users demonstrated improved overall survival (OS) and significantly improved recurrence-free survival (RFS) compared with non-users (median OS: not reached vs. 34 months [p = 0.072]; median RFS: not reached vs. 16 months [p = 0.031]). BB intake emerged as an independent prognostic factor in multivariable analysis for this subgroup (OS: hazard ratio [HR] 0.36, 95% confidence interval [CI] 0.17-0.76; RFS: HR 0.41, 95% CI 0.20-0.87). In contrast, BB use was associated with worse OS in intestinal subtype GC (median OS: 30 months vs. not reached; p = 0.044), an effect that diminished after adjusting for cardiovascular risk profiles. Higher ADRB2 expression was associated with less lymph node involvement in the DGC subtype (p = 0.030). - CONCLUSION: This study suggests a differential impact of BB use on GC subtypes and underscores the importance of considering cancer subtypes and patient comorbidities when evaluating the potential benefits of BBs in cancer therapy.
Gesehen am 10.10.2025